The Effectiveness of Audio-visual Media to Improve Students’ Writing Ability of Procedure Text - Masfa Maiza; Kunto Nurcahyoko (Journal of English Language Teaching and Islamic Integration, 2020)
As  writing  is  regarded  as  the  most  difficult  skill,  it  is  very challenging  for  teachers  to  teach  writing.  In  order  to  conduct  a  good writing  class,  the  application  of  media  can  be  one  of  the  alternative ways.  This  study  examines  the  effectiveness  of  using  audio-visual media to write a procedure text. This is a quasi-experimental study. The population of this study was the ninth graders of MTs Negeri 1 Landak and  the  sample  was  the  students  of  IX-A  and  IX-B.  The  method  of collecting data was test and field note, while t-test was used to analyze the  data.  The  analysis  of  writing  test  uses  the  components  of  writing namely organization, grammar and mechanics. The result shows that the students’ average of experimental group is higher that control group and the result of t-test gains that t value   > t table  = 7.05 > 1.99.  In addition, the use of  media also could  improve the students’ writing ability. Finally, this  media  is effective to use  in writing procedure text and the use of media would be useful for teachers and students.